Audit Report Lag Memediasi Pengaruh Financial Distress dan GCG pada Ketepatan Waktu Publikasi Laporan Keuangan - Nopayanti, Ni Luh Putu Ita; Ariyanto, Dodik (E-Jurnal Akuntansi, 2018)
G o pubic companies are required to submit audited financial statements in a timely manne r. Internal factors of the company and the independent auditor may affect the timeliness of financial statement publication . The purpose of this study is to obtain empirical evidence of the influence of financial distress and GCG on the timeliness of financial statement publication, with audit report lag as intervening variable. S amples are taken about 45 samples with purposive sampling method. Data was collect ed by non participant observation method. Data analysis technique us ing path analysis. The results showed that financial distress positively affect the audit report lag. GCG has a negative effect on audit report lag. Financial distress and GCG have no effect on the timeliness of financial statement publication . Financial distress and GCG affect the timeliness of financial statement publication through audit report lag. Keywords :  T imeliness of financial statement publication, financial distress, GCG, dan audit report lag